The Evaluation of Uterine Sarcomas: Tertiary Center Experience - Onur Yavuz; Kadir Alper Mankan; Asli Akdoner; Sultan Ot; Hasan Bahadir Saatli (Gynecology Obstetrics & Reproductive Medicine)
BJECTIVES: To elucidate prognostic factors, determine the best course of treatment methods, and assess oncological results in individuals diagnosed with uterine sarcoma.